Efforts and Factors in the Criminal Act of Iron Theft - T. Iskandar Faisal (International Journal For Advanced Research, 2025)
This study discusses the crime of iron theft that occurred in the jurisdiction of North Sumatra, by taking a case study of the case of T Iskandar Faisal. Iron theft cases have special characteristics because the stolen objects are not only of economic value, but also have social functions related to development and public interest. This study aims to analyze the application of criminal law to the crime of iron theft in accordance with the provisions of the Criminal Code (KUHP), specifically Article 362 concerning theft and the possibility of aggravation as regulated in Article 363 of the KUHP. The research method used is a normative juridical approach supported by case studies. Data were obtained through literature reviews, laws and regulations, court decisions, and relevant criminal law literature. The analysis was conducted qualitatively with an emphasis on normative aspects and practical implementation in the criminal justice process. The results of the study indicate that the application of the law to the crime of iron theft still faces a number of challenges, both in proving criminal elements and in the law enforcement process. Although Article 362 of the Criminal Code provides a legal basis, in practice, law enforcement officers often face obstacles in the form of limited evidence, testimony, and social factors underlying the crime. The case study of T Iskandar Faisal shows that while the legal process was carried out according to procedure, there are gaps that need to be addressed in the aspects of evidence and victim protection.